Different response rate to interferon in cgronic hepatitis B: importance of precore mutant and serum ferritin level - Yusuf BAYRAKTAR; Tankut KÖSEOĞLU; Aytekin TEMİZER and Gürol ÖKSÜZOĞLU and Durrişehver ÖZER and Bedri UZUNALİMOĞLU and Burhan KAYHAN (Turkish Journal of Gastroenterology, 2019)
-